The paradox of productivity: Reallocating labor and capital for economic diversification in Algeria - Kharchi, Tahar (Art Law and Accounting Reporter, 2025)
Algeria, a nation heavily reliant on hydrocarbon revenues, faces a critical juncture in its economic development. Despite periods of robust growth fueled by public spending, the country’s long-term prosperity is constrained by structural imbalances, notably a “productivity paradox” where high-growth sectors fail to absorb labor efficiently, while employment concentrates in low-value-added activities. This paper, grounded in the principles of economic geography, analyzes the recent macroeconomic trends (2022–2023) and the heterogeneous nature of sectoral productivity gains in Algeria. I find that while the agricultural and construction sectors have exhibited strong productivity growth, the manufacturing and high-value-added services sectors lag behind international peers. Furthermore, the persistent reliance on public expenditure has channeled employment towards non-commercial services and construction, sectors with limited long-term productivity potential. I argue that achieving sustainable, diversified, and resilient growth requires a fundamental shift in economic policy, focusing on strategic labor and capital reallocation towards high-productivity, non-hydrocarbon sectors, coupled with a disciplined fiscal consolidation strategy to mitigate the vulnerability posed by twin deficits.